Investigation of entomopathogenic fungi for control of false codling moth, Thaumatotibia leucotrata, Mediterranean fruit fly, Ceratitis capitata and Natal fruit fly, C. rosa in South African citrus - Goble, Tarryn Anne (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2010)
The biology of key citrus pests Thaumatotibia leucotreta Meyrick (Lepidoptera: Tortricidae), Ceratitis capitata Wiedemann (Diptera: Tephritidae) and Ceratitis rosa Karsch (Diptera: Tephritidae) includes their dropping from host plants to pupate in the soil below citrus trees. Since most EP fungi are soil-borne microorganisms, the development and formulation of alternative control strategies using these fungi as subterranean control agents, targeted at larvae and pupae in the soil, can potentially benefit existing IPM management of citrus in South Africa. Thus, a survey of occurrence of entomopathogenic fungi was undertaken on soils from citrus orchards and natural vegetation (refugia) on conventionally and organically managed farms in the Eastern Cape Province in South Africa. A method for baiting soil samples with citrus pest T. leucotreta and C. capitata larvae, as well as with the standard bait insect, Galleria mellonella Linnaeus (Lepidoptera: Pyralidae), was implemented. Sixty-two potentially useful entomopathogenic fungal isolates belonging to four genera were collected from 288 soil samples, an occurrence frequency of 21.53%. The most frequently isolated entomopathogenic fungal species was Beauveria bassiana (Balsamo) Vuillemin (15.63%), followed by Metarhizium anisopliae var. anisopliae (Metschnikoff) Sorokin (3.82%). Galleria mellonella was the most effective insect used to isolate fungal species (Ï‡2=40.13, df=2, Pâ‰¤ 0.005), with a total of 45 isolates obtained, followed by C. capitata with 11 isolates, and T. leucotreta with six isolates recovered. There was a significantly (Ï‡2=11.65, df=1, Pâ‰¤ 0.005) higher occurrence of entomopathogenic fungi in soil samples taken from refugia compared to cultivated orchards of both organically and conventionally managed farms. No significant differences were observed in the recovery of fungal isolates when soil samples from both farming systems were compared. The physiological effects and host range of 21 indigenous fungal isolates obtained in the Eastern Cape were investigated in the laboratory to establish whether these isolates could be effectively used as biological control agents against the subterranean life stages of C. rosa, C. capitata and T. leucotreta. When these pests were treated with a fungal concentration of 1 x 10â · conidia mlâ »Â¹, the percentage of T. leucotreta adults which emerged in fungal treated sand ranged from 5 to 60% (F=33.295; df=21; P=0.0001) depending on fungal isolate and the percentage of pupae with visible signs of mycosis ranged from 21 to 93% (F= 96.436; df=21; P=0.0001). Based on fungal isolates, the percentage adult survival in C. rosa and C. capitata ranged from 30 to 90% and 55 to 86% respectively. The percentage of C. rosa and C. capitata puparia with visible signs of mycosis ranged from 1 to 14% and 1 to 11% respectively. Deferred mortality due to mycosis in C. rosa and C. capitata adult flies ranged from 1 to 58% and 1 to 33% respectively, depending on fungal isolate. Entomopathogenic fungal isolates had a significantly greater effect on the adults of C. rosa and C. capitata than they did on the puparia of these two fruit fly species. Further, C. rosa and C. capitata did not differ significantly in their response to entomopathogenic fungi when adult survival or adult and pupal mycosis were considered. The relative potency of the four most virulent Beauveria isolates as well as the commercially available Beauveria bassiana product, Bb PlusÂ® (Biological Control Products, South Africa), were compared against one another as log-probit regressions of mortality against C. rosa, C. capitata and T. leucotreta which all exhibited a dose-dependent response. Against fruit flies the estimated LC50 values of all five Beauveria isolates ranged from 5.5 x 10Â¹Â¹ to 2.8 x 10Â¹Â² conidia/mlâ »Â¹. There were no significant differences between the relative potencies of these five fungal isolates. When T. leucotreta was considered, isolates: G Moss R10 and G 14 2 B5 and Bb PlusÂ® were significantly more pathogenic than G B Ar 23 B3 and FCM 10 13 L1. The estimated LCâ‚…â‚€ values of the three most pathogenic isolates ranged from 6.8 x 10â µ to 2.1 x 10â ¶ conidia/mlâ »Â¹, while those of the least pathogenic ranged from 1.6 x 10â · to 3.7 x 10â · conidia/mlâ »Â¹. Thaumatotibia leucotreta final instar larvae were exposed to two conidial concentrations, at four different exposure times (12, 48, 72 and 96 hrs) and showed an exposure time-dependant relationship (F=5.43; df=3; P=0.001). At 1 x 10â ·conidia/mlâ »Â¹ two Beauveria isolates: G Moss R10 and G 14 2 B5 were able to elicit a response in 50% of test insects at 72 hrs (3 days) exposure. Although a limited amount of mycosis was observed in the puparia of both fruit fly species, deferred adult mortality due to mycosis was high. The increased incidence of adult mortality suggests that post emergence mycosis in adult fruit flies may play a more significant role in field suppression than the control of fruit flies at the pupal stage. The increased incidence of pupal mortality, as well as the relatively low concentrations of conidia required to elicit meaningful responses in T. leucotreta pupae may suggest that pre-emergent control of false codling moth will play a more significant role in field suppression than the control of adult life stages using indigenous isolates of entomopathogenic fungi. Various entomopathogenic fungal application techniques targeted at key insect pests within integrated pest management (IPM) systems of citrus are discussed.
Keywords: Insect pests -- Biological control; Tortricidae -- Biological control -- South Africa; Tephritidae -- Biological control -- South Africa; Citrus -- Diseases and pests -- Biological control -- South Africa; Entomopathogenic fungi; Fungi as biological pest control agents; Biological pest control agents